The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1186/1472-6882-14-338
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture stimulation improves scopolamine-induced cognitive impairment via activation of cholinergic system and regulation of BDNF and CREB expressions in rats

Abstract: BackgroundAcupuncture is an alternative therapy that is widely used to treat various neurodegenerative diseases and effectively improve cognitive and memory impairment. The aim of this study was to examine whether acupuncture stimulation at the Baihui (GV20) acupoint improves memory defects caused by scopolamine (SCO) administration in rats. We also investigated the effects of acupuncture stimulation at GV20 on the cholinergic system as well as the expression of brain-derived neurotrophic factor (BDNF) and cAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
81
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(89 citation statements)
references
References 61 publications
6
81
0
Order By: Relevance
“…injection of scopolamine causes memory impairment, in accordance with previous investigations [4,18]. Scopolamine is a tropane alkaloid drug that exhibits competitive antagonism at muscarinic acetylcholine receptors (mAChRs) by interfering with cholinergic transmission in the central nervous system (CNS) [16,17]. Moreover, scopolamine administration to animals is used as an experimental model of the cognitive deterioration and memory disturbances in AD.…”
Section: Discussionmentioning
confidence: 56%
“…injection of scopolamine causes memory impairment, in accordance with previous investigations [4,18]. Scopolamine is a tropane alkaloid drug that exhibits competitive antagonism at muscarinic acetylcholine receptors (mAChRs) by interfering with cholinergic transmission in the central nervous system (CNS) [16,17]. Moreover, scopolamine administration to animals is used as an experimental model of the cognitive deterioration and memory disturbances in AD.…”
Section: Discussionmentioning
confidence: 56%
“…Although Creb and Bdnf gene expressions increased with MA, the expressions were not significantly higher than the expressions in the impaired rats. Considering that several previous studies have shown the regulation of CREB and BDNF neurotrophic signaling by MA stimulation of the points GV20 [47] and HT7 [19], the limited upregulation of Creb and Bdnf gene expressions shown by MA after cognitive impairment in this study was unexpected. One possible explanation for this discrepancy is the difference in the methods used to induce cognitive impairment.…”
Section: Discussionmentioning
confidence: 59%
“…One possible explanation for this discrepancy is the difference in the methods used to induce cognitive impairment. While cognitive impairment was induced via MCAO surgery in the present study, in the previous studies, cognitive impairment was induced via repeated administration of either corticosterone [19] or scopolamine [47]. The model-dependent effects of MA on cognitive deficit cannot be completely explained, and further studies are required to elucidate the differences in the effects of MA in diverse cognitive deficit models.…”
Section: Discussionmentioning
confidence: 80%
“…M. inermis significantly reversed this effect by decreasing the escape latency time prolonged by scopolamine, suggesting also the remembering on the platform by these mice [49, 50]. MWM is used as a device to investigate spatial learning and memory and for the validation of rodent models for neurocognitive disorders and the evaluation of possible neurocognitive treatments [52].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, these results suggest that M. inermis improves long-term and reference memory impairments induced by scopolamine [50, 51, 53, 54]. …”
Section: Discussionmentioning
confidence: 99%